The Effect of Bilingualism on Cue-Based vs. Memory-Based Task Switching in Older Adults - Rieker, Jennifer A.; Reales, José Manuel; Ballesteros, Soledad (Frontiers in Human Neuroscience, 2020)
Findings suggest a positive impact of bilingualism on cognition, including later onset of dementia. However, it is not clear to what extent these effects are influenced by variations in attentional control demands in response to specific task requirements. In this study, 20 bilingual and 20 monolingual older adults performed a task-switching task under explicit task-cuing versus memory-based switching conditions. In the cued condition, task switches occurred in a random order and a visual cue signalled the next task to be performed. In the memory-based condition, the task alternated after every second trial in a predictable sequence without presenting a cue. The performance of bilinguals did not vary across experimental conditions, whereas monolinguals experienced a pronounced increase in response latencies and error rates in the cued condition. Both groups produced similar switch costs (difference in performance on switch trials as opposed to repeat trials within the mixed-task block) and mixing costs (difference in performance on repeat trials of a mixed-task block as opposed to trials of a single-task block), but bilinguals produced them with lower response latencies. The cognitive benefits of bilingualism seem not to apply to executive functions per se but to affect specific cognitive processes that involve task-relevant context processing. The present results suggest that lifelong bilingualism could promote in older adults a flexible adjustment to environmental cues, but only with increased task demands. However, due to the small sample size, the results should be interpreted with caution. ent to environmental cues, but only with increased task demands.